Strategi Mengembangkan Modal Sosial Kelompok Wanita Tani (KWT) Dalam Meningkatkan Ketahanan Pangan dan Kesetaraan Gender - Setyadika, Shyellin Putri; Dwicahyo, Bambang Kusumo; Ma'rifah, Devi Cahyati; Putri, Cantika; Prasetyo, Ratna Azis (Antroposen: Journal of Social Studies and Humaniora, 2024)
The purpose of this research is to understand the role of social capital as well as to understand the strategies of KWT Merak and KWT Merak Jaya in improving food security and gender equality in Manuk Village, Ponorogo Regency, how women demonstrate their role in the form of implementing knowledge and skills in agriculture. Food security shown through this research is seen from 6 dimensions, namely availability, access, utilization, stability, agency, and sustainability. The method used was observation of the two demonstration plots and members' yards and indepth interviews with the heads and members of KWT Merak and KWT Merak Jaya to explore their processes in managing the groups. From the data, data interpretation was conducted in accordance with the problem formulation.  The strategy of KWT Merak and KWT Merak Jaya in improving food security and gender equality is seen from their independence to earn income that can help the economy, to cooperation with the support of the village government to continue this group. The strategy in question is in accordance with the theory of social capital by Robert D. Putnam which reviews social capital from values/norms, trust, and networks between agents in a group.